TPU (Thermoplastic Polyurethane) aggregate for film with high bonding strength with base cloth and TPU film prepared from TPU aggregate

By adopting TPU pellets for membranes with specific formulas, the aging and peeling problems of TPU films under the influence of ultraviolet rays and water vapor are solved, and the TPU film with high binding strength, good mechanical properties and long life is achieved, which enhances the market competitiveness of the product .

CN119391165APending Publication Date: 2025-02-07JIAXING HEXIN CHEM IND
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411565284.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing TPU films are prone to yellowing and aging and interlayer peeling under the influence of ultraviolet rays and water vapor, resulting in reduced mechanical properties and affecting service life.

Method used

A new type of TPU pellet for membranes is adopted, which consists of diisocyanate, chain extender composition, polyol, catalyst, functional filler and functional additive. By adjusting the formulation and process flow, the mechanical properties of the TPU film are improved. , weathering and hydrolysis resistance and heat processing resistance.

Benefits of technology

It significantly improves the bonding strength between the TPU film and the base cloth, extends the service life of the TPU film, improves the market competitiveness of the product, and optimizes the production cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of thermoplastic polyurethane elastomers, in particular to TPU (thermoplastic polyurethane) granules for a film with high bonding strength with base cloth and a TPU film prepared from the TPU granules, the shore hardness of the TPU granules for the film is 90-96A, the hardness content R value is 40-48%, and the TPU granules for the film are prepared from diisocyanate, a chain extender composition, polyol, a catalyst, functional filler and a functional aid; the chain extender composition comprises a micromolecular diol chain extender and a heat-resistant modified dianhydride chain extender, and the heat-resistant modified dianhydride chain extender is at least one of 1, 4-difluoro-2, 3, 5, 6-benzene tetracarboxylic dianhydride, 2, 6-dibromonaphthalene-1, 4, 5, 8-tetracarboxylic dianhydride and 1, 2, 4, 5-cyclohexanetetracarboxylic dianhydride. The TPU film prepared by the invention is high in bonding strength with base cloth, excellent in mechanical property, weather resistance, hydrolysis resistance and heat-resistant processability and relatively long in service life, and the market competitiveness of a product is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of thermoplastic polyurethane elastomer preparation, and in particular to a TPU granular material for membrane with high bonding strength with a base fabric and a TPU membrane prepared using the same. Background Art

[0002] Compared with other thermoplastic elastomer materials, thermoplastic polyurethane elastomer TPU has comprehensive advantages in wear resistance, elasticity, mechanical properties, etc. Its special physical and chemical properties mainly lie in the special soft and hard segment block copolymer structure of the molecular chain. The TPU molecular chain basically has no cross-linking structure, and its strength mainly depends on the covalent bond force of the molecular chain and the van der Waals force and hydrogen bond between macromolecular chains. The covalent bond force of the molecular chain refers to the TPU polymer main chain structure, that is, the soft and hard segment block copolymer structure, and the van der Waals force and hydrogen bond between macromolecular chains refer to the polymerized structure between TPU molecular chains.

[0003] A hydrogen atom is covalently bonded to an atom X with high electronegativity. If it is close to an atom Y (O, N, F, etc.) with high electronegativity and small radius, a special intermolecular or intramolecular interaction of the form XH...Y is generated between X and Y with hydrogen as the medium, which is called a hydrogen bond.

[0004] Specifically, the hardness and physical and chemical properties of TPU mainly depend on the molecular chain structure of the soft segment and hard segment in the macromolecular chain, the ratio of the soft segment to the hard segment (R value), the polarity and crystallinity of the molecular chain structure of the soft segment and the hard segment. The polarity and crystallinity of the molecular chain structure of the hard segment determine the ability to form hydrogen bonds. The hydrogen bond content in TPU depends on the number and distribution of polar O, N, and F atoms in the molecular chain structure, which affects the physical and chemical properties of TPU.

[0005] The hard segment limits the mobility of the molecular chain in the macromolecular chain. The greater the hard segment content, the weaker the mobility of the molecular chain. It preferentially gathers together and arranges regularly to form an ordered hard segment phase. The ordered hard segment phase will separate from the soft segment to form a microphase separation, that is, a microcrystalline area. The microcrystalline area acts as a cross-linking point of the material. The more microcrystalline areas there are, the better the hardness, wear resistance and mechanical strength of TPU, but its elongation at break and toughness are relatively low.

[0006] The TPU composite fabric in the prior art includes a base fabric, a PUR hot melt adhesive, and a TPU film. The TPU film is made of 85-96A TPU granules for film. The existing TPU film is limited by the influence of the TPU resin granules used. The isocyanate index in the TPU raw material design is about 1-1.02, which can improve the heat resistance to a certain extent. The isocyanate index in the PUR hot melt adhesive raw material design is usually above 1.08, which can ensure the bonding strength between the PUR hot melt adhesive and the substrate. There is good cohesion between the TPU film and the PUR hot melt adhesive, and the bonding strength between the two is acceptable. However, the TPU composite fabric is used as a sunscreen fabric in clothing such as windbreakers and assault jackets. It will be affected by ultraviolet rays and water vapor, causing the TPU film layer to be prone to yellowing and aging, interlayer peeling and detachment, and the mechanical properties of the TPU film are also reduced, affecting its service life. For this reason, the present invention provides a TPU granule for film with high bonding strength with the base fabric and a TPU film prepared using the same. Summary of the invention

[0007] In order to solve the above technical problems, the present application provides a TPU granular material for membrane with high bonding strength with a base fabric and a TPU film prepared using the same. The TPU film prepared using the obtained TPU granular material for membrane has good mechanical properties, hydrolysis resistance, and heat-resistant processing properties, and has a relatively long service life, thereby improving the market competitiveness of the product.

[0008] In the first aspect, the present application provides a TPU pellet for a membrane with high bonding strength with a base fabric, which is achieved by the following technical solutions: A TPU pellet for a film with high bonding strength to a base fabric has a Shore hardness of 90-96A and a hardness content R value of 40-48%; the TPU pellet for a film with high bonding strength to a base fabric comprises the following raw materials: diisocyanate, a chain extender composition, a polyol, a catalyst, a functional filler, and a functional additive; The ratio of the molar amount of NCO in the diisocyanate to the total molar amount of the active functional groups in the chain extender composition and the active functional groups in the polyol is 0.985-0.995; The chain extender composition includes a small molecule diol chain extender and a heat-resistant modified dianhydride chain extender; The heat-resistant modified dianhydride chain extender is at least one of 1,4-difluoro-2,3,5,6-pyromellitic dianhydride, 2.6-dibromonaphthalene-1,4,5,8-tetracarboxylic dianhydride, and 1,2,4,5-cyclohexanetetracarboxylic dianhydride; The small molecule diol chain extender is at least one of 1,5-pentanediol, 1,6-hexanediol, ethylene glycol, 1,4-butanediol, 1,3-propylene glycol, neopentyl glycol, diethylene glycol, and 3-methyl-1,5-pentanediol; The catalyst is organic bismuth or organic tin; The functional filler accounts for 5-10wt% of the total mass of the TPU pellets for the film with high bonding strength with the base fabric; The functional additives account for 2-5wt% of the total mass of the TPU pellets with high bonding strength with the base fabric; The functional additives at least include a defoamer, a leveling agent, an antioxidant, and an anti-ultraviolet agent.

[0009] The polyol is composed of a polycarbonate diol with a molecular weight of 800-2000 and at least one of a polyester polyol with a molecular weight of 1000-3000 and a polyether polyol with a molecular weight of 1000-3000; the polycarbonate diol with a molecular weight of 800-2000 accounts for 45-65wt% of the total mass of the polyol; The functional filler is composed of nano titanium dioxide particles, titanium dioxide nanotubes, halloysite nanotubes with an average particle size of 50-200nm and a pore opening agent with a particle size of 40-120 microns. The pore opening agent includes at least one of spherical or nearly spherical alumina, silicon dioxide, titanium dioxide, silicon carbide, and aluminum nitride.

[0010] In this application, a combination of heat-resistant modified dianhydride chain extender and functional filler is used to improve the heat-resistant processing performance of the prepared TPU, and the softening temperature is above 180°C, which solves the shrinkage problem of the TPU film caused by the processing temperature of PUR hot melt adhesive at around 150°C. In this application, a polyol formed by compounding polycarbonate diol with polyester polyol and polyether polyol is used. The TPU film prepared therefrom has good wear resistance, hydrolysis resistance, and mechanical properties, while reducing the amount of polycarbonate diol used, which is beneficial to the cost optimization of the TPU film. The functional filler used in this application is formed by compounding nano-titanium dioxide particles, titanium dioxide nanotubes, and halloysite nanotubes with a pore-opening agent, which can effectively improve the mechanical strength, UV resistance, heat resistance, and flame retardancy of TPU, and at the same time, it forms waterproof and breathable pores during the biaxial stretching process to improve the air permeability of TPU.

[0011] In the present application, the ratio of the NCO molar amount in the diisocyanate to the total molar amount of the active functional groups in the chain extender composition and the active functional groups in the polyol is 0.985-0.995, and the residual -OH group reacts with the NCO group in the PUR hot melt adhesive, which can effectively improve the bonding strength between the TPU film and the PUR hot melt adhesive. In summary, the TPU film in the present application has a high bonding strength with the base fabric, and has excellent mechanical properties, weather resistance and hydrolysis resistance, and heat resistance processing performance, has a relatively long service life, and improves the market competitiveness of the product.

[0012] Preferably, the diisocyanate is composed of an aliphatic diisocyanate and an aromatic diisocyanate, the aromatic diisocyanate accounts for 20-25wt% of the total mass of the diisocyanate, the aliphatic diisocyanate is at least one of hexamethylene diisocyanate HDI, cyclohexane-1,4-diisocyanate CHDI, isophorone diisocyanate IPDI, hydrogenated phenylmethane diisocyanate H12MDI, and 1,3-bis(isocyanatomethyl)cyclohexane; the aromatic diisocyanate is at least one of carbodiimide-modified MDI diisocyanate and 3,3'.-dimethoxy-4,4'-biphenyl diisocyanate.

[0013] Preferably, the aliphatic diisocyanate is hexamethylene diisocyanate HDI or hydrogenated phenylmethane diisocyanate H12MDI; and the aromatic diisocyanate is carbodiimide-modified MDI diisocyanate.

[0014] Preferably, the mass ratio of hexamethylene diisocyanate HDI, hydrogenated phenylmethane diisocyanate H12MDI, and carbodiimide-modified MDI diisocyanate is 50:(25-30):(20-25).

[0015] By adopting the above technical solution, the yellowing resistance and hydrolysis stability of the prepared TPU can be improved while having good mechanical strength.

[0016] Preferably, the chain extender composition is composed of a small molecule diol chain extender and a heat-resistant modified dianhydride chain extender in a mass ratio of (50-75):(25-50).

[0017] Preferably, the small molecule diol chain extender is 3-methyl-1,5-pentanediol or 1,4-butanediol.

[0018] Preferably, the heat-resistant modified dianhydride chain extender includes at least 1,4-difluoro-2,3,5,6-pyromellitic dianhydride.

[0019] By adjusting the composition of the heat-resistant modified dianhydride chain extender and the small molecule diol chain extender, the mechanical strength, hydrolysis resistance and heat resistance of the TPU pellets can be improved. At the same time, the content of 1,4-difluoro-2,3,5,6-benzenetetracarboxylic dianhydride can be optimized and adjusted to improve the bonding strength between the TPU film and the PUR hot melt adhesive.

[0020] Preferably, the chain extender composition is composed of 3-methyl-1,5-pentanediol, 1,4-butanediol, 1,4-difluoro-2,3,5,6-pyromellitic dianhydride, and 1,2,4,5-cyclohexanetetracarboxylic dianhydride, wherein the 1,4-difluoro-2,3,5,6-pyromellitic dianhydride accounts for 10-25wt% of the total mass of the chain extender composition; and the 1,2,4,5-cyclohexanetetracarboxylic dianhydride accounts for 15-25wt% of the total mass of the chain extender composition.

[0021] By adopting the above technical solution, the TPU pellets can be given good mechanical strength, hydrolysis resistance and heat resistance, and the prepared TPU film and PUR hot melt adhesive have relatively good bonding strength.

[0022] Preferably, the chain extender composition is composed of 3-methyl-1,5-pentanediol, 1,4-butanediol, 2.6-dibromonaphthalene-1,4,5,8-tetracarboxylic dianhydride, and 1,2,4,5-cyclohexanetetracarboxylic dianhydride, wherein the 2.6-dibromonaphthalene-1,4,5,8-tetracarboxylic dianhydride accounts for 10-25wt% of the total mass of the chain extender composition; and the 1,2,4,5-cyclohexanetetracarboxylic dianhydride accounts for 15-25wt% of the total mass of the chain extender composition.

[0023] By adopting the above technical scheme, not only can the TPU pellets be given good mechanical strength, hydrolysis resistance, and heat resistance, and the prepared TPU film and PUR hot melt adhesive can have relatively good bonding strength, but also good flame retardant properties can be given to it. When combined with functional fillers, the flame retardant performance reaches V0.

[0024] In the second aspect, the present application provides a TPU film prepared by using TPU pellets for film with high bonding strength with a base fabric, which is achieved by the following technical solutions: A TPU film prepared by using TPU granules for film with high bonding strength with a base fabric, the specific preparation method comprises the following steps: Step 1, respectively dehydrating the small molecule diol and the polyol in the chain extender composition, the dehydration method is as follows: heating to 110-120° C. for dehydration for at least 1 hour; Step 2: After DMF solvent, polyol, diisocyanate and catalyst are uniformly mixed, the temperature is raised to 85-90° C. under nitrogen protection, and the reaction is stirred at a constant temperature until the viscosity of the reactant is 1500-2500 mPa·s to obtain a prepolymer solution; the mass ratio of the DMF solvent to the polyol is 1:(0.6-1.2); the catalyst added to the prepolymer solution accounts for 50-75wt% of the total catalyst mass; Step 3, dissolving the remaining catalyst and the heat-resistant modified dianhydride chain extender in NMP solvent, and mixing them evenly to obtain a mixed solution; the mass ratio of NMP solvent to the heat-resistant modified dianhydride chain extender is 1:(0.5-1); the prepolymer solution is heated to 55-65°C, the stirring speed is maintained at 100-200rpm, and the mixed solution A is added dropwise to the prepolymer solution at 4-8g / min. After the mixed solution is added dropwise, the temperature is maintained at 55-65°C for 60-80min; Step 4, heating to 85-90°C, maintaining a stirring speed of 100-200rpm, adding a small molecule diol chain extender to the prepolymer solution at a rate of 4-8g / min, maintaining a temperature of 85-90°C for reaction for 1-2h after the addition of the small molecule diol chain extender, and then heating to 115-120°C for reaction for 1-2h to obtain a TPU resin stock solution; Step 5, pouring the TPU resin stock solution into a polytetrafluoroethylene mold with a mold temperature of 85-90°C, removing the NMP solvent and DMF solvent in the TPU resin stock solution by vacuum distillation, demolding after curing, and placing the obtained TPU sheet at room temperature for 2-6 days and then crushing it into TPU pellets at low temperature, and drying the obtained TPU pellets in a fluidized bed dryer at 80-85°C for 10-15 minutes until the water content is less than 0.03%, and then performing heat adjustment at 80-85°C for 20-24 hours to obtain TPU pellets for finished film; Step six, the TPU pellets for the finished film are placed in a twin-screw extruder for melt extrusion, and the resulting extruded melt is cast, biaxially stretched, cooled to form a film, cut, and rolled to obtain the finished TPU film.

[0025] By adopting the above preparation method, TPU pellets with excellent mechanical properties, weather resistance and hydrolysis resistance, and heat resistance and processing performance can be prepared. The TPU film prepared using the TPU pellets has excellent mechanical properties, weather resistance and hydrolysis resistance, and heat resistance and processing performance, and has a relatively long service life, thereby improving the market competitiveness of the product.

[0026] By adopting the above technical solution,

[0027] In summary, this application has the following advantages: 1. The TPU film prepared in this application has high bonding strength with the base fabric, and has excellent mechanical properties, weather resistance and hydrolysis resistance, and heat resistance and processing performance. It has a relatively long service life and improves the market competitiveness of the product.

[0028] 2. The preparation method of the present application is relatively simple, has low operating difficulty, and is easy to implement industrial production. DETAILED DESCRIPTION

[0029] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples and comparative examples. Example

[0030] A TPU pellet for film with high bonding strength to a base fabric has a Shore hardness of 90-96A and a hardness content R value of 40-48%. The -OH in the TPU pellet is appropriately excessive, so that the -OH in the TPU formed forms urethane with the NCO in the PUR hot melt adhesive, thereby improving the bonding stability of the two.

[0031] The invention discloses a TPU granular material for a film with high bonding strength with a base cloth, which is made of the following raw materials: diisocyanate, a chain extender composition, a polyol, a catalyst, a functional filler and a functional auxiliary agent.

[0032] The ratio of the molar amount of NCO in the diisocyanate to the total molar amount of the active functional groups in the chain extender composition and the active functional groups in the polyol is 0.985-0.995.

[0033] The chain extender composition comprises a small molecule diol chain extender and a heat-resistant modified dianhydride chain extender.

[0034] The heat-resistant modified dianhydride chain extender is at least one of 1,4-difluoro-2,3,5,6-benzenetetracarboxylic dianhydride, 2.6-dibromonaphthalene-1,4,5,8-tetracarboxylic dianhydride, and 1,2,4,5-cyclohexanetetracarboxylic dianhydride.

[0035] The small molecule diol chain extender is at least one of 1,5-pentanediol, 1,6-hexanediol, ethylene glycol, 1,4-butanediol, 1,3-propylene glycol, neopentyl glycol, diethylene glycol, and 3-methyl-1,5-pentanediol.

[0036] Preferably, the chain extender composition is composed of a small molecule diol chain extender and a heat-resistant modified dianhydride chain extender in a mass ratio of (50-75):(25-50), the small molecule diol chain extender is 3-methyl-1,5-pentanediol and 1,4-butanediol, and the heat-resistant modified dianhydride chain extender includes at least 1,4-difluoro-2,3,5,6-benzenetetracarboxylic dianhydride.

[0037] Further preferably, the chain extender composition is composed of 3-methyl-1,5-pentanediol, 1,4-butanediol, 1,4-difluoro-2,3,5,6-pyromellitic dianhydride and 1,2,4,5-cyclohexanetetracarboxylic dianhydride, wherein 1,4-difluoro-2,3,5,6-pyromellitic dianhydride accounts for 10-25wt% of the total mass of the chain extender composition, and 1,2,4,5-cyclohexanetetracarboxylic dianhydride accounts for 15-25wt% of the total mass of the chain extender composition.

[0038] Further preferably, the chain extender composition is composed of 3-methyl-1,5-pentanediol, 1,4-butanediol, 2.6-dibromonaphthalene-1,4,5,8-tetracarboxylic dianhydride, and 1,2,4,5-cyclohexanetetracarboxylic dianhydride, wherein 2.6-dibromonaphthalene-1,4,5,8-tetracarboxylic dianhydride accounts for 10-25wt% of the total mass of the chain extender composition; and 1,2,4,5-cyclohexanetetracarboxylic dianhydride accounts for 15-25wt% of the total mass of the chain extender composition.

[0039] Diisocyanates are composed of aliphatic diisocyanates and aromatic diisocyanates.

[0040] The aromatic diisocyanate accounts for 20-25 wt % of the total mass of the diisocyanate.

[0041] The aliphatic diisocyanate is at least one of hexamethylene diisocyanate HDI, cyclohexane-1,4-diisocyanate CHDI, isophorone diisocyanate IPDI, hydrogenated phenylmethane diisocyanate H12MDI, and 1,3-bis(isocyanatomethyl)cyclohexane.

[0042] The aromatic diisocyanate is at least one of carbodiimide-modified MDI diisocyanate and 3,3'-dimethoxy-4,4'-biphenyl diisocyanate.

[0043] Preferably, the aliphatic diisocyanate is hexamethylene diisocyanate HDI or hydrogenated phenylmethane diisocyanate H12MDI, and the aromatic diisocyanate is carbodiimide-modified MDI diisocyanate.

[0044] The carbodiimide-modified MDI diisocyanate is Lupranate 5143, MM103, 219, 218, 81 in BASF carbodiimide-modified MDI. Preferably, the carbodiimide-modified MDI diisocyanate is Lupranate 5143, with an NCO content of 29.2% and a viscosity of 33 cps at 25°C.

[0045] More preferably, the mass ratio of hexamethylene diisocyanate HDI, hydrogenated phenylmethane diisocyanate H12MDI, and carbodiimide-modified MDI diisocyanate is 50:(25-30):(20-25).

[0046] The polyol is composed of a polycarbonate diol with a molecular weight of 800-2000 and at least one of a polyester polyol with a molecular weight of 1000-3000 and a polyether polyol with a molecular weight of 1000-3000. The polycarbonate diol with a molecular weight of 800-2000 in the polyol accounts for 45-65wt% of the total weight of the polyol.

[0047] The catalyst is organic bismuth or organic tin.

[0048] The organic bismuth is bismuth isooctanoate.

[0049] The organic tin is dibutyltin dilaurate or stannous octoate.

[0050] The functional filler accounts for 5-10wt% of the total mass of the TPU pellets for the film having a high bonding strength with the base fabric.

[0051] The functional filler is composed of nano titanium dioxide particles, titanium dioxide nanotubes, and halloysite nanotubes with an average particle size of 50-200 nm and a pore opening agent with a particle size of 40-120 microns. The pore opening agent includes at least one of spherical or nearly spherical aluminum oxide, silicon dioxide, titanium dioxide, silicon carbide, and aluminum nitride.

[0052] The functional additive accounts for 2-5wt% of the total mass of the TPU pellets for the film having high bonding strength with the base fabric.

[0053] The functional additives at least include a defoamer, a leveling agent, an antioxidant, and an anti-ultraviolet agent.

[0054] The defoaming agent is at least one of Evonik TEGO Airex 944, 963, and 990.

[0055] The leveling agent is BioRich S-3313 TPU leveling agent or Evonik TEGO Glide 110.

[0056] The antioxidant is at least one of antioxidant BHT, antioxidant 1010, antioxidant 1035, antioxidant 1076, antioxidant 1098, and antioxidant 168. The anti-ultraviolet agent is at least one of UV531, UV284, UV326, UV327, UV328, and UV320.

[0057] A method for preparing TPU pellets for membranes having high bonding strength with a base fabric comprises the following steps: Step 1, respectively dehydrating the small molecule diol and the polyol in the chain extender composition, the dehydration method is as follows: heating to 110-120° C. for dehydration for at least 1 hour; Step 2: After DMF solvent, polyol, diisocyanate and catalyst are uniformly mixed, the temperature is raised to 85-90° C. under nitrogen protection, and the reaction is stirred at a constant temperature until the viscosity of the reactant is 1500-2500 mPa·s to obtain a prepolymer solution; the mass ratio of the DMF solvent to the polyol is 1:(0.6-1.2); the catalyst added to the prepolymer solution accounts for 50-75wt% of the total catalyst mass; Step 3, dissolving the remaining catalyst and the heat-resistant modified dianhydride chain extender in NMP solvent, and mixing them evenly to obtain a mixed solution; the mass ratio of NMP solvent to the heat-resistant modified dianhydride chain extender is 1:(0.5-1); the prepolymer solution is heated to 55-65°C, the stirring speed is maintained at 100-200rpm, and the mixed solution A is added dropwise to the prepolymer solution at 4-8g / min. After the mixed solution is added dropwise, the temperature is maintained at 55-65°C for 60-80min; Step 4, heating to 85-90°C, maintaining a stirring speed of 100-200rpm, adding a small molecule diol chain extender to the prepolymer solution at a rate of 4-8g / min, maintaining a temperature of 85-90°C for reaction for 1-2h after the addition of the small molecule diol chain extender, and then heating to 115-120°C for reaction for 1-2h to obtain a TPU resin stock solution; Step 5, pour the TPU resin stock solution into a polytetrafluoroethylene mold with a mold temperature of 85-90°C, remove the NMP solvent and DMF solvent in the TPU resin stock solution by reduced pressure distillation, demold after curing, and place the obtained TPU sheet at room temperature for 2-6 days and then crush it into TPU pellets at low temperature. The obtained TPU pellets are dried in a fluidized bed dryer at 80-85°C for 10-15 minutes until the water content is less than 0.03%, and then heat-adjusted at 80-85°C for 20-24 hours to obtain TPU pellets for finished film.

[0058] A TPU film is prepared by using TPU pellets for film with high bonding strength with a base fabric. The preparation method of the TPU film is as follows: the TPU pellets for finished film are placed in a twin-screw extruder for melt extrusion, the obtained extruded melt is cast, biaxially stretched, cooled to form a film, and cut and rolled to obtain the finished TPU film.

[0059] Raw materials: Titanium dioxide nanotubes were prepared by anodization: first, the titanium foil sheet β-21S (provided by Guanhui Special Alloys) was ultrasonically cleaned (44kHz / 600W) for 30 minutes using ultrapure water, acetone, and anhydrous ethanol in turn, and then dried in an oven for use; at 25°C, the cleaned titanium foil sheet β-21S was used as the anode and the nickel sheet as the cathode, and an ethylene glycol solution with a mass fraction of 0.5wt% ammonium chloride and a volume fraction of 1vt% ultrapure water was used as the electrolyte. The reaction time was 45 minutes at a voltage of 40 V, and finally, ultrapure water, acetone, and anhydrous ethanol were ultrasonically cleaned (80kHz / 600W) for 60 minutes, respectively, until the nanotube array on the surface of the sample fell off. The product was filtered and vacuum dried to obtain titanium dioxide nanotubes.

[0060] Example 1: A TPU pellet for a film with high bonding strength to a base fabric is prepared from 131.2 g of 4, 4'-dicyclohexylmethane diisocyanate (Wanhua HMDI), 168.2 g of hexamethylene-1,6-diisocyanate (Wanhua HDI), 125.2 g of carbodiimide modified MDI (Wanhua CDMDI-100L), 44.9 g of 3-methyl-1,5-pentanediol, 54.1 g of 1,4-butanediol, 76.2 g of 1,2,4,5-cyclohexanetetracarboxylic acid anhydride (CAS No.: 6053-68-5), 76.3 g of 1,4-difluoro-2,3,5,6-benzenetetracarboxylic acid anhydride (CAS No.: 46861-94-3), 120g of poly(1,5-pentanediol adipate-3-methyl) (Kuraray P-2010, Japan), 180g of polytetramethylene glycol PTMEG (PoiyTHF 2000, BASF), 480g of poly(hexamethylene carbonate caprolactone) CD2220PL (Dacel Corporation, Japan), 0.62g of dibutyltin dilaurate, 32.5g of nano titanium dioxide particles (CW-TiO2-002, average particle size 30nm, Chaowei Nano), 32.5g of titanium dioxide nanotubes, 32.5g of halloysite nanotubes (purchased from Angxing New Carbon Materials Changzhou Co., Ltd.), 16.3g of spherical alumina with a particle size of 50 microns, 20g of TEGO Airex 944, and 16g of leveling agent - TEGO Glide 110, 12g of antioxidant BHT, 8g of UV531.

[0061] A method for preparing TPU pellets for membranes having high bonding strength with a base fabric comprises the following steps: Step 1: Dehydration treatment is performed on 44.9 g of 3-methyl-1,5-pentanediol, 54.1 g of 1,4-butanediol, 120 g of poly(3-methyl-1,5-pentanediol adipate) (Kuraray P-2010, Japan), 180 g of polytetrahydrofuran diol PTMEG (PoiyTHF 2000, BASF), and 480 g of poly(hexamethylene carbonate caprolactone) diol CD2220PL (Dacel Corporation, Japan) in the chain extender composition, respectively. The dehydration treatment method is as follows: heating to 120° C. for dehydration treatment for 1 hour; Step 2: 920 g of DMF solvent, 120 g of poly(3-methyl adipate-1,5-pentanediol) (Kuraray P-2010, Japan), 180 g of poly(tetrahydrofuran diol) PTMEG (BASF PoiyTHF 2000), 480 g of poly(caprolactone carbonate hexamethylene diol) CD2220PL (Dacel Corporation, Japan), 131.2 g of 4, 4'-dicyclohexylmethane diisocyanate, 168.2 g of hexamethylene-1,6-diisocyanate HDI, 125.2 g of carbodiimide-modified MDI, and 0.38 g of catalyst-dibutyltin dilaurate were mixed evenly, and the mixture was heated to 88° C. under nitrogen protection, and stirred at a constant temperature to react until the viscosity of the reactant was 1500-2500 mPa·s. The actual test viscosity of the reactant was 1680 mPa·s, and a prepolymer solution was obtained; Step 3: Dissolve the remaining 0.24g of the catalyst - dibutyltin dilaurate, 76.2g of 1,2,4,5-cyclohexanetetracarboxylic acid anhydride, and 76.3g of 1,4-difluoro-2,3,5,6-benzenetetracarboxylic acid anhydride in 200g of NMP solvent, heat the prepolymer solution to 60°C, maintain the stirring speed at 200rpm, and add the mixed solution A dropwise to the prepolymer solution at 5g / min. After the mixed solution is added dropwise, maintain the reaction at 60°C for 75min; Step 4, heating to 90°C, maintaining a stirring speed of 200rpm, adding a small molecule diol chain extender to the prepolymer solution at a rate of 4-8g / min, and after the addition of 44.9g of 3-methyl-1,5-pentanediol and 54.1g of 1,4-butanediol, maintaining a temperature of 90°C for 2h, and then heating to 115-120°C for 2h to obtain a TPU resin stock solution; Step 5, pour the TPU resin stock solution into a polytetrafluoroethylene mold with a mold temperature of 90°C, and remove the NMP solvent and DMF solvent in the TPU resin stock solution by reduced pressure distillation. After the curing is completed, demolding is performed, and the obtained TPU sheet is placed at room temperature for 5 days and then crushed into TPU pellets at low temperature. The obtained TPU pellets are dried in a fluidized bed dryer at 80°C for 10 minutes until the water content is less than 0.03%, and then thermally adjusted at 85°C for 24 hours to obtain TPU pellets for finished film.

[0062] A TPU film is prepared by using TPU pellets for film with high bonding strength with a base fabric. The preparation method of the TPU film is as follows: the TPU pellets for finished film are placed in a twin-screw extruder and melt-extruded at 200-225°C. The extruded melt is cast through a hot pressing roller to obtain a semi-finished film material with a thickness of 150 microns. Specifically, the set temperatures of seven heating temperature zones in the twin-screw extruder are as follows: 190°C / 200°C / 210°C / 220°C / 225°C / 225°C / 220°C, the die temperature is 220°C, L / D=24, the screw extrusion speed is 48rpm, the semi-finished film material is biaxially stretched at 85°C, the longitudinal stretching ratio is 2.5, the transverse stretching ratio is 1.2, and the biaxial stretching is followed by cooling to room temperature. The finished TPU film with an average film thickness of 50 microns is obtained by cutting and winding.

[0063] The difference between Example 2 and Example 1 is that a TPU pellet for a film with high bonding strength to a base fabric is composed of 131.2 g of 4, 4'-dicyclohexylmethane diisocyanate, 168.2 g of hexamethylene-1,6-diisocyanate HDI, 125.2 g of carbodiimide modified MDI, 44.9 g of 3-methyl-1,5-pentanediol, 54.1 g of 1,4-butanediol, 143.5 g of 1,2,4,5-cyclohexanetetracarboxylic acid anhydride, 120 g of polyadipate-3-methyl 1,5-pentanediol ester diol P-2010, 180 g of polytetrahydrofuran diol PTMEG PoiyTHF 2000, 480g of polycaprolactone hexamethylene glycol CD2220PL, 0.62g of dibutyltin dilaurate, 32.5g of nano titanium dioxide particles, 32.5g of titanium dioxide nanotubes, 32.5g of halloysite nanotubes, 16.3g of spherical alumina with a particle size of 50 microns, 20g of defoamer-TEGO Airex 944, 16g of leveling agent-TEGO Glide 110, 12g of antioxidant BHT, and 8g of UV531.

[0064] The difference between Example 3 and Example 1 is that a TPU pellet for a film with high bonding strength to a base fabric is composed of 131.2 g of 4, 4'-dicyclohexylmethane diisocyanate, 168.2 g of hexamethylene-1,6-diisocyanate HDI, 125.2 g of carbodiimide modified MDI, 44.9 g of 3-methyl-1,5-pentanediol, 54.1 g of 1,4-butanediol, 111.8 g of 1,4-difluoro-2,3,5,6-benzenetetracarboxylic acid anhydride, 85.2 g of 2.6-dibromonaphthalene-1,4,5,8-tetracarboxylic acid anhydride (CAS No.: 83204-68-6), 120 g of polyadipate-3-methyl 1,5-pentanediol ester diol P-2010, and 180 g of polytetrahydrofuran diol PTMEG PoiyTHF 2000, 480g of polycaprolactone hexamethylene glycol CD2220PL, 0.62g of dibutyltin dilaurate, 32.5g of nano titanium dioxide particles, 32.5g of titanium dioxide nanotubes, 32.5g of halloysite nanotubes, 16.3g of spherical alumina with a particle size of 50 microns, 20g of defoamer-TEGO Airex 944, 16g of leveling agent-TEGO Glide110, 12g of antioxidant BHT, and 8g of UV531.

[0065] The difference between Example 4 and Example 1 is that a TPU pellet for a film with high bonding strength to a base fabric is composed of 131.2 g of 4, 4'-dicyclohexylmethane diisocyanate, 168.2 g of hexamethylene-1,6-diisocyanate HDI, 125.2 g of carbodiimide modified MDI, 44.9 g of 3-methyl-1,5-pentanediol, 54.1 g of 1,4-butanediol, 162.2 g of 1,4-difluoro-2,3,5,6-benzenetetracarboxylic acid anhydride, 120 g of polyadipate-3-methyl 1,5-pentanediol ester diol P-2010, and 180 g of polytetrahydrofuran diol PTMEG PoiyTHF 2000, 480g of polycaprolactone hexamethylene glycol CD2220PL, 0.62g of dibutyltin dilaurate, 32.5g of nano titanium dioxide particles, 32.5g of titanium dioxide nanotubes, 32.5g of halloysite nanotubes, 16.3g of spherical alumina with a particle size of 50 microns, 20g of defoamer-TEGO Airex 944, 16g of leveling agent-TEGO Glide 110, 12g of antioxidant BHT, and 8g of UV531.

[0066] The difference between Example 5 and Example 1 is that a TPU pellet for a film with high bonding strength to a base fabric is composed of 131.2 g of 4, 4'-dicyclohexylmethane diisocyanate, 168.2 g of hexamethylene-1,6-diisocyanate HDI, 125.2 g of carbodiimide modified MDI, 44.9 g of 3-methyl-1,5-pentanediol, 54.1 g of 1,4-butanediol, 98.7 g of 1,2,4,5-cyclohexanetetracarboxylic acid anhydride, 85.2 g of 2.6-dibromonaphthalene-1,4,5,8-tetracarboxylic acid anhydride, 120 g of polyadipate-3-methyl 1,5-pentanediol ester diol P-2010, 180 g of polytetrahydrofuran diol PTMEG PoiyTHF 2000, 480g of polycaprolactone hexamethylene glycol CD2220PL, 0.62g of dibutyltin dilaurate, 32.5g of nano titanium dioxide particles, 32.5g of titanium dioxide nanotubes, 32.5g of halloysite nanotubes, 16.3g of spherical alumina with a particle size of 50 microns, 20g of defoamer-TEGO Airex 944, 16g of leveling agent-TEGO Glide 110, 12g of antioxidant BHT, and 8g of UV531.

[0067] The difference between Example 6 and Example 1 is that a TPU pellet for a film with high bonding strength to a base fabric is composed of 131.2 g of 4, 4'-dicyclohexylmethane diisocyanate, 168.2 g of hexamethylene-1,6-diisocyanate HDI, 125.2 g of carbodiimide modified MDI, 35.5 g of 3-methyl-1,5-pentanediol, 46.9 g of 1,4-butanediol, 100.9 g of 1,2,4,5-cyclohexanetetracarboxylic acid anhydride, 88.9 g of 1,4-difluoro-2,3,5,6-benzenetetracarboxylic acid anhydride, 120 g of polyadipate-3-methyl 1,5-pentanediol ester diol P-2010, and 180 g of polytetrahydrofuran diol PTMEG PoiyTHF 2000, 480g of polycaprolactone hexamethylene glycol CD2220PL, 0.62g of dibutyltin dilaurate, 32.5g of nano titanium dioxide particles, 32.5g of titanium dioxide nanotubes, 32.5g of halloysite nanotubes, 16.3g of spherical alumina with a particle size of 50 microns, 20g of defoamer-TEGO Airex 944, 16g of leveling agent-TEGO Glide 110, 12g of antioxidant BHT, and 8g of UV531.

[0068] The difference between Example 7 and Example 1 is that a TPU pellet for a film having high bonding strength with a base fabric is composed of 262.4 g of 4, 4'-dicyclohexylmethane diisocyanate, 168.2 g of hexamethylene-1,6-diisocyanate HDI, 44.9 g of 3-methyl-1,5-pentanediol, 54.1 g of 1,4-butanediol, 76.2 g of 1,2,4,5-cyclohexanetetracarboxylic acid anhydride, 76.3 g of 1,4-difluoro-2,3,5,6-benzenetetracarboxylic acid anhydride, 120 g of polyadipate-3-methyl 1,5-pentanediol ester diol P-2010, and 180 g of polytetrahydrofuran diol PTMEG PoiyTHF 2000, 480g of polycaprolactone hexamethylene glycol CD2220PL, 0.62g of dibutyltin dilaurate, 32.5g of nano titanium dioxide particles, 32.5g of titanium dioxide nanotubes, 32.5g of halloysite nanotubes, 16.3g of spherical alumina with a particle size of 50 microns, 20g of defoamer - TEGO Airex 944, 16g of TEGO Glide 110, 12g of antioxidant BHT, and 8g of UV531.

[0069] The difference between Example 8 and Example 1 is that a TPU pellet for a film with high bonding strength to a base fabric is composed of 252.3 g of hexamethylene-1,6-diisocyanate HDI, 148.2 g of 3,3'.-dimethoxy-4,4'-biphenyl diisocyanate, 44.9 g of 3-methyl-1,5-pentanediol, 54.1 g of 1,4-butanediol, 76.2 g of 1,2,4,5-cyclohexanetetracarboxylic acid anhydride, 76.3 g of 1,4-difluoro-2,3,5,6-benzenetetracarboxylic acid anhydride, 120 g of polyadipate-3-methyl 1,5-pentanediol ester diol P-2010, and 180 g of polytetrahydrofuran diol PTMEG PoiyTHF 2000, 480g of polycaprolactone hexamethylene glycol CD2220PL, 0.62g of dibutyltin dilaurate, 32.5g of nano titanium dioxide particles, 32.5g of titanium dioxide nanotubes, 32.5g of halloysite nanotubes, 16.3g of spherical alumina with a particle size of 50 microns, 20g of TEGO Airex 944, 16g of TEGO Glide 110, 12g of antioxidant BHT, and 8g of UV531.

[0070] The difference between Example 9 and Example 1 is that a TPU pellet for a film having high bonding strength with a base fabric is composed of 131.2 g of 4, 4'-dicyclohexylmethane diisocyanate, 168.2 g of hexamethylene-1,6-diisocyanate HDI, 148.2 g of 3,3'.-dimethoxy-4,4'-biphenyl diisocyanate, 44.9 g of 3-methyl-1,5-pentanediol, 54.1 g of 1,4-butanediol, 76.2 g of 1,2,4,5-cyclohexanetetracarboxylic acid anhydride, 76.3 g of 1,4-difluoro-2,3,5,6-benzenetetracarboxylic acid anhydride, 120 g of polyadipate-3-methyl 1,5-pentanediol ester diol P-2010, and 180 g of polytetrahydrofuran diol PTMEG polyyTHF. 2000, 480g of polycaprolactone hexamethylene glycol CD2220PL, 0.62g of dibutyltin dilaurate, 32.5g of nano titanium dioxide particles, 32.5g of titanium dioxide nanotubes, 32.5g of halloysite nanotubes, 16.3g of spherical alumina with a particle size of 50 microns, 20g of TEGO Airex 944, 16g of TEGO Glide 110, 12g of antioxidant BHT, and 8g of UV531.

[0071] The difference between Example 10 and Example 1 is that a TPU pellet for a film with high bonding strength to a base fabric is composed of 500.3 g of carbodiimide modified MDI, 44.9 g of 3-methyl-1,5-pentanediol, 54.1 g of 1,4-butanediol, 76.2 g of 1,2,4,5-cyclohexanetetracarboxylic acid anhydride, 76.3 g of 1,4-difluoro-2,3,5,6-benzenetetracarboxylic acid anhydride, 120 g of polyadipate-3-methyl-1,5-pentanediol ester diol P-2010, and 180 g of PTMEG PoiyTHF 2000, 480g of polycaprolactone hexamethylene glycol CD2220PL, 0.62g of dibutyltin dilaurate, 32.5g of nano titanium dioxide particles, 32.5g of titanium dioxide nanotubes, 32.5g of halloysite nanotubes, 16.3g of spherical alumina with a particle size of 50 microns, 20g of TEGO Airex 944, 16g of TEGO Glide 110, 12g of antioxidant BHT, and 8g of UV531.

[0072] The difference between Example 11 and Example 1 is that a TPU pellet for a film with high bonding strength to a base fabric is composed of 105.0 g of 4, 4'-dicyclohexylmethane diisocyanate, 168.2 g of hexamethylene-1,6-diisocyanate HDI, 150.2 g of carbodiimide modified MDI, 44.9 g of 3-methyl-1,5-pentanediol, 54.1 g of 1,4-butanediol, 76.2 g of 1,2,4,5-cyclohexanetetracarboxylic acid anhydride, 76.3 g of 1,4-difluoro-2,3,5,6-benzenetetracarboxylic acid anhydride, 120 g of polyadipate-3-methyl 1,5-pentanediol ester diol P-2010, 180 g of PTMEG PoiyTHF 2000, 480g of polycaprolactone hexamethylene glycol CD2220PL, 0.62g of dibutyltin dilaurate, 32.5g of nano titanium dioxide particles, 32.5g of titanium dioxide nanotubes, 32.5g of halloysite nanotubes, 16.3g of spherical alumina with a particle size of 50 microns, 20g of TEGO Airex 944, 16g of TEGO Glide 110, 12g of antioxidant BHT, and 8g of UV531.

[0073] The difference between Example 12 and Example 1 is that a TPU pellet for a film with high bonding strength to a base fabric is composed of 157.5 g of 4, 4'-dicyclohexylmethane diisocyanate, 147.8 g of hexamethylene-1,6-diisocyanate HDI, 150.2 g of carbodiimide modified MDI, 44.9 g of 3-methyl-1,5-pentanediol, 54.1 g of 1,4-butanediol, 76.2 g of 1,2,4,5-cyclohexanetetracarboxylic acid anhydride, 76.3 g of 1,4-difluoro-2,3,5,6-benzenetetracarboxylic acid anhydride, 120 g of polyadipate-3-methyl 1,5-pentanediol ester diol P-2010, 180 g of PTMEG PoiyTHF 2000, 480g of polycaprolactone hexamethylene glycol CD2220PL, 0.62g of dibutyltin dilaurate, 32.5g of nano titanium dioxide particles, 32.5g of titanium dioxide nanotubes, 32.5g of halloysite nanotubes, 16.3g of spherical alumina with a particle size of 50 microns, 20g of TEGO Airex 944, 16g of TEGO Glide 110, 12g of antioxidant BHT, and 8g of UV531.

[0074] The difference between Example 13 and Example 1 is that a TPU pellet for a film with high bonding strength to a base fabric is composed of 131.2 g of 4, 4'-dicyclohexylmethane diisocyanate, 168.2 g of hexamethylene-1,6-diisocyanate HDI, 125.2 g of carbodiimide modified MDI, 44.9 g of 3-methyl-1,5-pentanediol, 54.1 g of 1,4-butanediol, 76.2 g of 1,2,4,5-cyclohexanetetracarboxylic acid anhydride, 76.3 g of 1,4-difluoro-2,3,5,6-benzenetetracarboxylic acid anhydride, 120 g of polyadipate-3-methyl 1,5-pentanediol ester diol P-2010, 180 g of PTMEG PoiyTHF 2000, 480g of polycaprolactone hexamethylene glycol CD2220PL, 0.62g of dibutyltin dilaurate, 22.3g of nano titanium dioxide particles, 22.3g of titanium dioxide nanotubes, 22.3g of halloysite nanotubes, 12.8g of spherical alumina with a particle size of 50 microns, 20g of TEGO Airex 944, 16g of TEGO Glide 110, 12g of antioxidant BHT, and 8g of UV531.

[0075] The difference between Example 14 and Example 1 is that a TPU pellet for a film with high bonding strength to a base fabric is composed of 131.2 g of 4, 4'-dicyclohexylmethane diisocyanate, 168.2 g of hexamethylene-1,6-diisocyanate HDI, 125.2 g of carbodiimide modified MDI, 44.9 g of 3-methyl-1,5-pentanediol, 54.1 g of 1,4-butanediol, 76.2 g of 1,2,4,5-cyclohexanetetracarboxylic acid anhydride, 76.3 g of 1,4-difluoro-2,3,5,6-benzenetetracarboxylic acid anhydride, 120 g of polyadipate-3-methyl 1,5-pentanediol ester diol P-2010, 180 g of PTMEG PoiyTHF 2000, 480g of polycaprolactone hexamethylene glycol CD2220PL, 0.62g of dibutyltin dilaurate, 50.4g of nano titanium dioxide particles, 50.4g of titanium dioxide nanotubes, 50.4g of halloysite nanotubes, 16.8g of spherical alumina with a particle size of 50 microns, 20g of TEGO Airex 944, 16g of TEGO Glide 110, 12g of antioxidant BHT, and 8g of UV531.

[0076] The difference between Example 15 and Example 1 is that the compositions of nano-titanium dioxide particles, titanium dioxide nanotubes, halloysite nanotubes and pore opening agents in the functional filler are different.

[0077] A TPU pellet for film with high bonding strength with a base fabric is composed of 131.2g of 4, 4'-dicyclohexylmethane diisocyanate, 168.2g of hexamethylene-1,6-diisocyanate HDI, 125.2g of carbodiimide modified MDI, 44.9g of 3-methyl-1,5-pentanediol, 54.1g of 1,4-butanediol, 76.2g of 1,2,4,5-cyclohexanetetracarboxylic acid anhydride, 76.3g of 1,4-difluoro-2,3,5,6-benzenetetracarboxylic acid anhydride, 120g of polyadipate-3-methyl 1,5-pentanediol ester diol P-2010, and 180g of PTMEG PoiyTHF 2000, 480g of polycaprolactone hexamethylene glycol CD2220PL, 0.62g of dibutyltin dilaurate, 16.3g of nano titanium dioxide particles, 40.7g of titanium dioxide nanotubes, 40.7g of halloysite nanotubes, 16.3g of spherical alumina with a particle size of 50 microns, 20g of TEGO Airex 944, 16g of TEGO Glide 110, 12g of antioxidant BHT, and 8g of UV531.

[0078] The difference between Example 16 and Example 1 is that the functional filler is composed of nano titanium dioxide particles, halloysite nanotubes, and a pore opening agent.

[0079] A TPU pellet for film with high bonding strength with a base fabric is composed of 131.2g of 4, 4'-dicyclohexylmethane diisocyanate, 168.2g of hexamethylene-1,6-diisocyanate HDI, 125.2g of carbodiimide modified MDI, 44.9g of 3-methyl-1,5-pentanediol, 54.1g of 1,4-butanediol, 76.2g of 1,2,4,5-cyclohexanetetracarboxylic acid anhydride, 76.3g of 1,4-difluoro-2,3,5,6-benzenetetracarboxylic acid anhydride, 120g of polyadipate-3-methyl 1,5-pentanediol ester diol P-2010, and 180g of PTMEG PoiyTHF 2000, 480g of polycaprolactone hexamethylene glycol CD2220PL, 0.62g of dibutyltin dilaurate, 48.8g of nano titanium dioxide particles, 48.8g of halloysite nanotubes, 16.3g of spherical alumina with a particle size of 50 microns, 20g of TEGO Airex 944, 16g of TEGO Glide 110, 12g of antioxidant BHT, and 8g of UV531.

[0080] The difference between Example 17 and Example 1 lies in the composition of nano-titanium dioxide particles, titanium dioxide nanotubes and pore opening agent in the functional filler.

[0081] A TPU pellet for film with high bonding strength with a base fabric is composed of 131.2g of 4, 4'-dicyclohexylmethane diisocyanate, 168.2g of hexamethylene-1,6-diisocyanate HDI, 125.2g of carbodiimide modified MDI, 44.9g of 3-methyl-1,5-pentanediol, 54.1g of 1,4-butanediol, 76.2g of 1,2,4,5-cyclohexanetetracarboxylic acid anhydride, 76.3g of 1,4-difluoro-2,3,5,6-benzenetetracarboxylic acid anhydride, 120g of polyadipate-3-methyl 1,5-pentanediol ester diol P-2010, and 180g of PTMEG PoiyTHF 2000, 480g of polycaprolactone hexamethylene glycol CD2220PL, 0.62g of dibutyltin dilaurate, 48.8g of nano titanium dioxide particles, 48.8g of titanium dioxide nanotubes, 16.3g of spherical alumina with a particle size of 50 microns, 20g of TEGO Airex 944, 16g of TEGO Glide 110, 12g of antioxidant BHT, and 8g of UV531.

[0082] The difference between Example 18 and Example 1 lies in the composition of the nano-titanium dioxide particles and the pore opening agent in the functional filler.

[0083] A TPU pellet for film with high bonding strength with a base fabric is composed of 131.2g of 4, 4'-dicyclohexylmethane diisocyanate, 168.2g of hexamethylene-1,6-diisocyanate HDI, 125.2g of carbodiimide modified MDI, 44.9g of 3-methyl-1,5-pentanediol, 54.1g of 1,4-butanediol, 76.2g of 1,2,4,5-cyclohexanetetracarboxylic acid anhydride, 76.3g of 1,4-difluoro-2,3,5,6-benzenetetracarboxylic acid anhydride, 120g of polyadipate-3-methyl 1,5-pentanediol ester diol P-2010, and 180g of PTMEG PoiyTHF 2000, 480g of polycaprolactone hexamethylene glycol CD2220PL, 0.62g of dibutyltin dilaurate, 97.6g of nano titanium dioxide particles, 16.3g of spherical alumina with a particle size of 50 microns, 20g of TEGO Airex944, 16g of TEGO Glide 110, 12g of antioxidant BHT, and 8g of UV531.

[0084] The difference between Comparative Example 1 and Example 1 is that a TPU pellet for a membrane having high bonding strength with a base fabric is composed of 500.6 g of 4,4'-diisocyanate diphenylmethane (Wanhua MDI-100), 73.3 g of 3-methyl-1,5-pentanediol, 90.2 g of 1,4-butanediol, 120 g of polyadipate-3-methyl-1,5-pentanediol ester diol (Japan Kuraray P-2010), 180 g of polytetrahydrofuran diol PTMEG (BASF PoiyTHF 2000), 480 g of polycarbonate caprolactone hexamethylene diol CD2220PL (Japan Daicel Corporation), 0.62 g of dibutyltin dilaurate, 97.6 g of nano titanium dioxide particles, 16.3 g of spherical alumina with a particle size of 50 microns, and 20 g of a defoaming agent - TEGO Airex 944, 16g of leveling agent-TEGO Glide 110, 12g of antioxidant BHT, 8g of UV531.

[0085] The difference between Comparative Example 2 and Example 1 is that a TPU pellet for a film with high bonding strength to a base fabric is composed of 500.6 g of 4,4'-diisocyanate diphenylmethane (Wanhua MDI-100), 73.3 g of 3-methyl-1,5-pentanediol, 90.2 g of 1,4-butanediol, 120 g of poly(1,5-pentanediol adipate-3-methyl adipate) (Japan Kuraray P-2010), 180 g of poly(tetrahydrofuran diol) PTMEG (BASF PoiyTHF 2000), 480g of polycaprolactone hexamethylene glycol CD2220PL (Dacelide Co., Ltd., Japan), 0.62g of dibutyltin dilaurate, 32.5g of nano titanium dioxide particles, 32.5g of titanium dioxide nanotubes, 32.5g of halloysite nanotubes, 16.3g of spherical alumina with a particle size of 50 microns, 20g of defoamer - TEGO Airex 944, 16g of leveling agent - TEGO Glide 110, 12g of antioxidant BHT, and 8g of UV531.

[0086] The difference between Comparative Example 3 and Example 1 is that a TPU pellet for a membrane with high bonding strength to a base fabric is composed of 262.4 g of 4, 4'-dicyclohexylmethane diisocyanate, 168.2 g of hexamethylene-1,6-diisocyanate HDI, 73.3 g of 3-methyl-1,5-pentanediol, 90.2 g of 1,4-butanediol, 780 g of polycarbonate caprolactone hexamethylene glycol CD2220PL, 0.62 g of dibutyltin dilaurate, 97.6 g of nano titanium dioxide particles, 16.3 g of spherical alumina with a particle size of 50 microns, 20 g of defoaming agent-TEGO Airex 944, 16 g of leveling agent-TEGO Glide 110, 12 g of antioxidant BHT, and 8 g of UV531.

[0087] The difference between Comparative Example 4 and Example 1 is that a TPU pellet for film with high bonding strength with the base fabric is composed of 262.4g of 4, 4'-dicyclohexylmethane diisocyanate, 168.2g of hexamethylene-1,6-diisocyanate HDI, 73.3g of 3-methyl-1,5-pentanediol, 90.2g of 1,4-butanediol, 120g of poly(1,5-pentanediol adipate-3-methyl adipate) (Japan Kuraray P-2010), 180g of poly(tetramethylene glycol) PTMEG (BASF PoiyTHF 2000), 480g of polycaprolactone hexamethylene glycol CD2220PL (Dacelide Co., Ltd., Japan), 0.62g of dibutyltin dilaurate, 32.5g of nano titanium dioxide particles, 32.5g of titanium dioxide nanotubes, 32.5g of halloysite nanotubes, 16.3g of spherical alumina with a particle size of 50 microns, 20g of defoamer - TEGO Airex 944, 16g of leveling agent - TEGO Glide 110, 12g of antioxidant BHT, and 8g of UV531.

[0088] The difference between Comparative Example 5 and Example 1 is that a TPU pellet for a film having high bonding strength with a base fabric is prepared by mixing 131.2 g of 4,4'-dicyclohexylmethane diisocyanate, 168.2 g of hexamethylene-1,6-diisocyanate HDI, 125.2 g of carbodiimide-modified MDI, 44.9 g of 3-methyl-1,5-pentanediol, 54.1 g of 1,4-butanediol, 76.2 g of 1,2,4,5-cyclohexanetetracarboxylic acid anhydride, and 76.3 g of 1,4-difluoro-2,3,5,6-benzenetetracarboxylic acid anhydride. anhydride, 120g of poly(3-methyl 1,5-pentanediol adipate) P-2010, 180g of poly(tetramethylenetetrahydrofuran) glycol PTMEG (BASF PoiyTHF2000), 480g of poly(hexamethylene carbonate) caprolactone glycol CD2220PL, 0.62g of dibutyltin dilaurate, 16.3g of spherical alumina with a particle size of 50 microns, 20g of defoamer - TEGO Airex 944, 16g of leveling agent - TEGO Glide 110, 12g of antioxidant BHT, and 8g of UV531.

[0089] The difference between Comparative Example 6 and Example 1 is that a TPU pellet for a film with high bonding strength to a base fabric is composed of 131.2 g of 4, 4'-dicyclohexylmethane diisocyanate, 168.2 g of hexamethylene-1,6-diisocyanate HDI, 125.2 g of carbodiimide modified MDI, 44.9 g of 3-methyl-1,5-pentanediol, 54.1 g of 1,4-butanediol, 76.2 g of 1,2,4,5-cyclohexanetetracarboxylic acid anhydride, 76.3 g of 1,4-difluoro-2,3,5,6-benzenetetracarboxylic acid anhydride, 120 g of poly 3-Methyl 1,5-pentanediol adipate P-2010, 180g of polytetramethylene glycol PTMEG (BASF PoiyTHF2000), 480g of polycaprolactone hexamethylene glycol CD2220PL, 0.62g of dibutyltin dilaurate, 32.5g of nano titanium dioxide particles, 16.3g of spherical alumina with a particle size of 50 microns, 20g of defoamer - TEGO Airex 944, 16g of leveling agent - TEGO Glide 110, 12g of antioxidant BHT, and 24g of UV531.

[0090] The TPU film prepared from the above TPU pellets has the problem of UV531 precipitation and has a relatively short service life.

[0091] The difference between Comparative Example 7 and Example 1 is that a TPU pellet for a film with high bonding strength to a base fabric is composed of 131.2 g of 4, 4'-dicyclohexylmethane diisocyanate, 168.2 g of hexamethylene-1,6-diisocyanate HDI, 125.2 g of carbodiimide modified MDI, 44.9 g of 3-methyl-1,5-pentanediol, 54.1 g of 1,4-butanediol, 76.2 g of 1,2,4,5-cyclohexanetetracarboxylic acid anhydride, 76.3 g of 1,4-difluoro-2,3,5,6-benzenetetracarboxylic acid anhydride, 120 g of poly(1,5-difluoro-3-methyl-1,5-pentanediol) and 1,2,4,5-cyclohexanetetracarboxylic acid anhydride. Ester diol P-2010, 180g of polytetramethylene glycol PTMEG (BASF PoiyTHF2000), 480g of polycaprolactone hexamethylene glycol CD2220PL, 0.62g of dibutyltin dilaurate, 10.9g of nano titanium dioxide particles, 10.9g of titanium dioxide nanotubes, 10.9g of halloysite nanotubes, 12.5g of spherical alumina with a particle size of 50 microns, 20g of defoamer - TEGO Airex 944, 16g of leveling agent - TEGO Glide 110, 12g of antioxidant BHT, and 8g of UV531.

[0092] The difference between Comparative Example 8 and Example 1 is that a TPU pellet for a film with high bonding strength to a base fabric is composed of 131.2 g of 4, 4'-dicyclohexylmethane diisocyanate, 168.2 g of hexamethylene-1,6-diisocyanate HDI, 125.2 g of carbodiimide modified MDI, 44.9 g of 3-methyl-1,5-pentanediol, 54.1 g of 1,4-butanediol, 76.2 g of 1,2,4,5-cyclohexanetetracarboxylic acid anhydride, 76.3 g of 1,4-difluoro-2,3,5,6-benzenetetracarboxylic acid anhydride, 120 g of poly(1,5-difluoro-3-methyl-1,5-pentanediol) and 1,2,4,5-cyclohexanetetracarboxylic acid anhydride. Ester diol P-2010, 180g of polytetramethylene glycol PTMEG (BASF PoiyTHF2000), 480g of polycaprolactone hexamethylene glycol CD2220PL, 0.62g of dibutyltin dilaurate, 69.4g of nano titanium dioxide particles, 69.4g of titanium dioxide nanotubes, 69.4g of halloysite nanotubes, 13.9g of spherical alumina with a particle size of 50 microns, 20g of defoamer - TEGO Airex 944, 16g of leveling agent - TEGO Glide 110, 12g of antioxidant BHT, and 8g of UV531.

[0093] Performance test: 1. Tensile performance test method: Determine according to the DIN 53504-S2 test method. 2. Jungle test test method: After the sample is aged at 80°C and 85% humidity for 3 weeks, the tensile performance is determined according to the DIN 53504-S2 test method, and the tear strength is determined according to the DIN 53515 test method. 3. Tear strength test method: Determine according to the DIN 53515 test method. 4. Softening point temperature: The TPU pellets in Examples 1-18 and Comparative Examples 1-8 are made into TPU films, and the obtained TPU films are cut into 30cm*25cm as test samples. The two ends of the test sample are tied with wires, one end is hung with a paper clip, and the other end is hung with three paper clips, and the film is separated from the release paper. Hang the threaded test sample in the oven (one paper clip is hung on the top, and three paper clips are hung on the bottom), turn on the oven, and record the temperature when the paper clip at the lower end touches the bottom of the oven, which is the softening point temperature of the resin. 5. Washing resistance test method: The sample (microfiber cloth / PUR adhesive / TPU film) is washed 10 times according to the GB / T8629-2017 standard 5N procedure, then tumble dried at 70°C, and the wetness rating is tested by the water dipping method. 6. Adhesive strength test: According to GB / T 2791-1995 Adhesive T peel strength test method, flexible material to flexible material is measured.

[0094] Table 1: Physical and chemical parameters of the TPU pellets prepared in Examples 1-18 and Comparative Examples 1-8

[0095] It can be seen from Examples 1-18 and Comparative Example 1 and Table 1 that the TPU pellets prepared in the present application have relatively good weather resistance and hydrolysis resistance, and have a relatively long service life, and the mechanical properties and heat-resistant processing properties of the TPU pellets are similar to those of the TPU pellets in Comparative Example 1.

[0096] Combining Examples 1-18 and Comparative Examples 1-3 and Table 1, it can be seen that the functional fillers formed by nano-titanium dioxide particles, titanium dioxide nanotubes, halloysite nanotubes, and spherical alumina with a particle size of 50 microns can improve the physical and chemical properties of TPU pellets, and the filler addition amount is preferably controlled at 5-10wt%.

[0097] It can be seen from Examples 1-18 and Comparative Example 4 and Table 1 that the TPU pellets prepared by the chain extender composition formed by the small molecule diol chain extender and the heat-resistant modified dianhydride chain extender have relatively excellent comprehensive physical and chemical properties, can ensure weather resistance and hydrolysis resistance while improving mechanical strength, and have a relatively wide range of applications.

[0098] It can be seen from Examples 1-18 and Comparative Examples 5-6 and Table 1 that the functional fillers formed by nano-titanium dioxide particles, titanium dioxide nanotubes, halloysite nanotubes, and spherical alumina with a particle size of 50 microns can significantly improve the weather resistance of TPU pellets, while improving the heat resistance and mechanical strength of TPU pellets.

[0099] From Examples 1-18 and Comparative Examples 7-8 and Table 1, it can be seen that the addition amount of the functional filler formed by nano-titanium dioxide particles, titanium dioxide nanotubes, halloysite nanotubes, and spherical alumina with a particle size of 50 microns is preferably controlled at 5-10wt%. Too little addition will have a corresponding reinforcement effect, while too much addition will affect the tensile properties of the TPU pellets and increase the production cost, which is not conducive to industrial mass production.

[0100] Table 2: Bonding strength parameters of TPU films and PUR adhesives in Examples 1-18 and Comparative Examples 1-8

[0101] Note: The PUR adhesive used in the test is hot melt pressure sensitive adhesive 4000E, provided by Shanghai Hongchong New Material Technology Co., Ltd. The TPU film in the control group is the PU moisture permeable film WS-DZ025B of Weisai New Materials.

[0102] It can be seen from Examples 1-18 and Comparative Examples 7-8 and Table 1-2 that the TPU film in the present application has a high bonding strength with the base fabric, and the peel strength retention rate at -25°C to 80°C is above 75%. The -OH group contained in the TPU film will react with the -NCO group in the PUR glue to enhance the final bonding strength and bonding stability; and the TPU film has excellent mechanical properties (tensile strength ≥50MPa, fracture productivity ≥550%), weather resistance and hydrolysis resistance (hydrolysis resistance retention rate ≥88%), and heat resistance (softening point temperature ≥175°C), and has a relatively long service life.

Claims

1. A TPU pellet for film with high bonding strength with a base fabric, characterized in that: The TPU pellets for membranes with high bonding strength to the base fabric have a Shore hardness of 90-96A and a hardness content R value of 40-48%; the TPU pellets for membranes with high bonding strength to the base fabric are made of the following raw materials: diisocyanate, chain extender composition, polyol, catalyst, functional filler, and functional additive; The ratio of the molar amount of NCO in the diisocyanate to the total molar amount of the active functional groups in the chain extender composition and the active functional groups in the polyol is 0.985-0.995; The chain extender composition includes a small molecule diol chain extender and a heat-resistant modified dianhydride chain extender; The heat-resistant modified dianhydride chain extender is at least one of 1,4-difluoro-2,3,5,6-pyromellitic dianhydride, 2.6-dibromonaphthalene-1,4,5,8-tetracarboxylic dianhydride, and 1,2,4,5-cyclohexanetetracarboxylic dianhydride; The small molecule diol chain extender is at least one of 1,5-pentanediol, 1,6-hexanediol, ethylene glycol, 1,4-butanediol, 1,3-propylene glycol, neopentyl glycol, diethylene glycol, and 3-methyl-1,5-pentanediol; The catalyst is organic bismuth or organic tin; The functional filler accounts for 5-10wt% of the total mass of the TPU pellets for the film with high bonding strength with the base fabric; The functional additives account for 2-5wt% of the total mass of the TPU pellets with high bonding strength with the base fabric; The functional additives at least include a defoamer, a leveling agent, an antioxidant, and an anti-ultraviolet agent.

2. The TPU pellets for membranes with high bonding strength with base fabric according to claim 1, characterized in that: The diisocyanate is composed of an aliphatic diisocyanate and an aromatic diisocyanate, wherein the aromatic diisocyanate accounts for 20-25wt% of the total mass of the diisocyanate, and the aliphatic diisocyanate is at least one of hexamethylene diisocyanate HDI, cyclohexane-1,4-diisocyanate CHDI, isophorone diisocyanate IPDI, hydrogenated phenylmethane diisocyanate H12MDI, and 1,3-bis(isocyanatomethyl)cyclohexane; and the aromatic diisocyanate is at least one of carbodiimide-modified MDI diisocyanate and 3,3'.-dimethoxy-4,4'-biphenyl diisocyanate.

3. The TPU pellets for membranes with high bonding strength with base fabric according to claim 2, characterized in that: The aliphatic diisocyanate is hexamethylene diisocyanate HDI or hydrogenated phenylmethane diisocyanate H12MDI; the aromatic diisocyanate is carbodiimide-modified MDI diisocyanate.

4. The TPU granules for membranes with high bonding strength with base fabric according to claim 3, characterized in that: The mass ratio of the hexamethylene diisocyanate HDI, hydrogenated phenylmethane diisocyanate H12MDI, and carbodiimide-modified MDI diisocyanate is 50:(25-30):(20-25).

5. The TPU pellets for membranes with high bonding strength with base fabric according to claim 1, characterized in that: The chain extender composition is composed of a small molecule diol chain extender and a heat-resistant modified dianhydride chain extender in a mass ratio of (50-75):(25-50), wherein the small molecule diol chain extender is 3-methyl-1,5-pentanediol and 1,4-butanediol; and the heat-resistant modified dianhydride chain extender at least includes 1,4-difluoro-2,3,5,6-pyromellitic dianhydride.

6. The TPU pellets for membranes with high bonding strength with base fabric according to claim 5, characterized in that: The chain extender composition is composed of 3-methyl-1,5-pentanediol, 1,4-butanediol, 1,4-difluoro-2,3,5,6-pyromellitic acid anhydride and 1,2,4,5-cyclohexanetetracarboxylic acid anhydride, wherein the 1,4-difluoro-2,3,5,6-pyromellitic acid anhydride accounts for 10-25wt% of the total mass of the chain extender composition; and the 1,2,4,5-cyclohexanetetracarboxylic acid anhydride accounts for 15-25wt% of the total mass of the chain extender composition.

7. The TPU pellets for membranes with high bonding strength with base fabric according to claim 5, characterized in that: The chain extender composition is composed of 3-methyl-1,5-pentanediol, 1,4-butanediol, 2.6-dibromonaphthalene-1,4,5,8-tetracarboxylic dianhydride and 1,2,4,5-cyclohexanetetracarboxylic dianhydride, wherein the 2.6-dibromonaphthalene-1,4,5,8-tetracarboxylic dianhydride accounts for 10-25wt% of the total mass of the chain extender composition; and the 1,2,4,5-cyclohexanetetracarboxylic dianhydride accounts for 15-25wt% of the total mass of the chain extender composition.

8. The TPU pellets for membranes with high bonding strength with base fabric according to claim 1, characterized in that: The polyol is composed of a polycarbonate diol with a molecular weight of 800-2000 and at least one of a polyester polyol with a molecular weight of 1000-3000 and a polyether polyol with a molecular weight of 1000-3000; the polycarbonate diol with a molecular weight of 800-2000 accounts for 45-65wt% of the total mass of the polyol.

9. The TPU pellets for membranes with high bonding strength with base fabric according to claim 1, characterized in that: The functional filler is composed of nano titanium dioxide particles, titanium dioxide nanotubes, halloysite nanotubes with an average particle size of 50-200nm and a pore opening agent with a particle size of 40-120 microns. The pore opening agent includes at least one of spherical or nearly spherical alumina, silicon dioxide, titanium dioxide, silicon carbide, and aluminum nitride.

10. A TPU film prepared by using the TPU pellets for film with high bonding strength with a base fabric according to any one of claims 1 to 9, characterized in that: The method for preparing the TPU film comprises the following steps: Step 1, respectively dehydrating the small molecule diol and the polyol in the chain extender composition, the dehydration method is as follows: heating to 110-120° C. for dehydration for at least 1 hour; Step 2: After DMF solvent, polyol, diisocyanate and catalyst are uniformly mixed, the temperature is raised to 85-90° C. under nitrogen protection, and the reaction is stirred at a constant temperature until the viscosity of the reactant is 1500-2500 mPa·s to obtain a prepolymer solution; the mass ratio of the DMF solvent to the polyol is 1:(0.6-1.2); the catalyst added to the prepolymer solution accounts for 50-75wt% of the total catalyst mass; Step 3, dissolving the remaining catalyst and the heat-resistant modified dianhydride chain extender in NMP solvent, and mixing them evenly to obtain a mixed solution; the mass ratio of NMP solvent to the heat-resistant modified dianhydride chain extender is 1:(0.5-1); the prepolymer solution is heated to 55-65°C, the stirring speed is maintained at 100-200rpm, and the mixed solution A is added dropwise to the prepolymer solution at 4-8g / min. After the mixed solution is added dropwise, the temperature is maintained at 55-65°C for 60-80min; Step 4, heating to 85-90°C, maintaining a stirring speed of 100-200rpm, adding a small molecule diol chain extender to the prepolymer solution at a rate of 4-8g / min, maintaining a temperature of 85-90°C for reaction for 1-2h after the addition of the small molecule diol chain extender, and then heating to 115-120°C for reaction for 1-2h to obtain a TPU resin stock solution; Step 5, pouring the TPU resin stock solution into a polytetrafluoroethylene mold with a mold temperature of 85-90°C, removing the NMP solvent and DMF solvent in the TPU resin stock solution by vacuum distillation, demolding after curing, and placing the obtained TPU sheet at room temperature for 2-6 days and then crushing it into TPU pellets at low temperature, and drying the obtained TPU pellets in a fluidized bed dryer at 80-85°C for 10-15 minutes until the water content is less than 0.03%, and then performing heat adjustment at 80-85°C for 20-24 hours to obtain TPU pellets for finished film; Step six, the TPU pellets for the finished film are placed in a twin-screw extruder for melt extrusion, and the resulting extruded melt is cast, biaxially stretched, cooled to form a film, cut, and rolled to obtain the finished TPU film.